Comprehensive Clinical Plasma Medicine Cold Physical Plasma for Medical Application (Springer International Publishing, 2018)
This book presents the state of the art in clinical plasma medicine and outlines translational research strategies. Written by an international group of authors, it is divided into four parts. Part I is a detailed introduction and includes basic and recent research information on plasma sciences, plasma devices and mechanisms of biological plasma effects. Parts II and III provide valuable clinical insights f.e. into the treatment of superficial contaminations, ulcerations, wounds, treatment of cells in cancer, special indications like in heart surgery, dentistry, palliative treatment in head and neck cancer or the use of plasma in hygiene. Part IV offers information on how and where to qualify in plasma medicine and which companies produce and supply medical devices and is thus of particular interest to medical practitioners. This comprehensive book offers a sciences based practical to the clinical use of plasma and includes an extended selection of scien tific medical data and translational literature.